Gendered anthropology - Valle Teresa Del (London : Routledge, 1993)
In the last three decades, a remarkable degree of progress has occurred in the study of gender within anthropology. Gendered Anthropology offers a thought-provoking, lively examination of current debates focusing on sex and gender, race, ethnicity, politics and economics and provides insights which are still too often lacking in mainstream anthropology.Gendered Anthropology will be of particular value to undergraduates and lecturers in social anthropology and gender studies.
Includes references 205-219p.; Index 220-227p.
Keywords: Gendered anthropology; Anthropology